Intravital Imaging Allows Organ-Specific Insights Into Immune Functions - Jorch, Selina K.; Deppermann, Carsten (Frontiers in Cell and Developmental Biology, 2021)
Leukocytes are among the most mobile and versatile cells that have many functions that are essential for homeostasis and survival. Especially cells from the innate immune system, i.e. neutrophils and macrophages, play an important role as rapid first responders against invading microorganisms. With the advent of novel imaging techniques, new ways of visualizing innate immune cells have become available in recent years, thereby enabling more and more detailed discoveries about their nature, function and interaction partners. Besides intravital spinning-disc and 2-photon microscopy, clearing and 3D imaging techniques provided new insights into the mechanism of innate immune cell behavior in their natural environment. This mini review focuses on the contributions of novel imaging techniques to provide insight into the functions of neutrophils and macrophages under homeostasis and in infections. Imaging setups for different organs like the liver, kidney, heart, lung and the peritoneal cavity are discussed as well as the current limitations of these imaging techniques.